Utilization of Biosolids in Forage Production Systems in Florida - Maria L. Silveira; George A. O'Connor; Joao M. B. Vendramini (EDIS)
This four-page publication provides basic information about land application of biosolids to pastures and hayfields in Florida. The information contained in this document should be of interest to stakeholders, biosolids managers, students, and scientists interested in topics related to biosolids management practices and the potential benefits and risks associated with biosolid land application. Written by Maria L. Silveira, George A. O’Connor, and Joao M.B. Vendramini and published by the Department of Soil and Water Sciences.